A prospective material for the highly selective extraction of lithium ions based on a photochromic crowned spirobenzopyran. Issue 6 (18th January 2019) - Li, Enze; Kang, Jin; Ye, Peiyuan; Zhang, Weijie; Cheng, Fangqin; Yin, Caixia
Abstract : The recovery of lithium from salt lake brines with a high Mg/Li ratio continues to be a challenge due to the very similar ionic properties of Li + and Mg 2+ in aqueous solutions. Abstract : The recovery of lithium from salt lake brines with a high Mg/Li ratio continues to be a challenge due to the very similar ionic properties of Li + and Mg 2+ in aqueous solutions. Here we develop a novel strategy to extract Li + based on a sensitive photochromic crowned spiropyran probe with the control of UV light. The probe presents high selectivity for Li + complexation even in solutions with a high Mg/Li ratio up to 1000. On this basis, a high-stability "spiropyran-crown ether" polymer composite membrane material for the visualization and efficient extraction of trace lithium ions in the complicated system of salt lake brines with high ionic strengths will be constructed in the future.